Performance Characteristics of Miniature Photovoltaic Farm Under Dynamic Partial Shading - Antonius Rajagukguk; Dedet Candra Riawan; Mochamad Ashari (Institute of Advanced Engineering and Science, 2018)
This paper presents investigation of performance characteristic on a miniature photovoltaic farm under dynamic partially shaded condition. Effects of applying bypass diodes in each photovoltaics modul and the transient current of the diode is also investigated. The miniature of PV Farm consisting 4 photovoltaic panels, connected in series to form one string. The whole system comprises 5 photovoltaic strings, which are connected in parallel producing 30 volt and 60 watt peak power fromminiature PV farm. Shading of 10%, 20 % up to 50 % with dynamically changed is applied. Result from both laboratory tests and simulations is investigated and show very similar.